L’étude de l’activité antibactérienne d’huile essentielle de Salvia officinalis .L sur deux souches (E.coli et Staphylococcus aureus) - BERRAHAL, SARA; BESSEDIK, IBTISSEM (My University, 2020)
The emergence of pathogen microorganisms is currently a public health concern. Indeed, the resistance of germs to antibiotics makes sometimes the therapeutic treatment inefficient and requires the search for new antimicrobial agents. The use of medicinal plants is then one of the most interesting paths to explore; it is in this perspective that we were interested to study the antibacterial activity of essential oil of Mostaganem’s sage (salvia officinalis). In this study, we performed the extraction of essential oils from the leaves of plant and the evaluation of its antibacterial activity against some potentially pathogenic bacteria. The antibacterial test revealed that the essential oil passes an interesting antibacterial effect principally against E.coli. The recorded inhibition zone (Ø= 15mm) slightly exceeds those caused by vancomycin (Ø= 14mm). These results are promising and provide a scientific validation to the massive use of this species. Thus the effect of natural substances extracted from medicinal plants may well rival that of antibiotics.
Keywords: antibacterial activity; salvia officinalis; essential oils; antibiotics